ANIMAL OBSERVATION METHODS IN A ZOOLOGY COURSE - E. K. Joldasbaeva (Scholars Digest Publishing, 2024)
In this article, it is stated that one of the factors that strengthen the knowledge gained in the classroom when teaching the zoology lesson to students in the school is that the lesson should be conducted in connection with an excursion and that they can get more information through the methods of observing animals.
Keywords: zoophenological observation, methods of observation, tools and equipment needed in the lesson of observation.